Emerging Biosensing Technologies for the Diagnostics of Viral Infectious Diseases. Issue 30 (5th April 2022) - Kabay, Gözde; DeCastro, Jonalyn; Altay, Alara; Smith, Kasey; Lu, Hsiang‐Wei; Capossela, Antonia McDonnell; Moarefian, Maryam; Aran, Kiana; Dincer, Can
Abstract: Several viral infectious diseases appear limitless since the beginning of the 21 st century, expanding into pandemic lengths. Thus, there are extensive efforts to provide more efficient means of diagnosis, a better understanding of acquired immunity, and improved monitoring of inflammatory biomarkers, as these are all crucial for controlling the spread of infection while aiding in vaccine development and improving patient outcomes. In this regard, various biosensors have been developed recently to streamline pathogen and immune response detection by addressing the limitations of traditional methods, including isothermal amplification‐based systems and lateral flow assays. This review explores state‐of‐the‐art biosensors for detecting viral pathogens, serological assays, and inflammatory biomarkers from the material perspective, by discussing their advantages, limitations, and further potential regarding their analytical performance, clinical utility, and point‐of‐care adaptability. Additionally, next‐generation biosensing technologies that offer better sensitivity and selectivity, and easy handling for end‐users are highlighted. An emerging example of these next‐generation biosensors are those powered by novel synthetic biology tools, such as clustered regularly interspaced short palindromic repeats (CRISPR) with CRISPR‐associated proteins (Cas), in combination with integrated point‐of‐care devices. Lastly, the current challenges are discussed and a roadmap for furthering these advanced biosensing technologies to manage future pandemics is provided. Abstract : State‐of‐the‐art biosensors successfully assist differentiative diagnosis and screening of viral pathogens and related biomarkers for facilitating the pandemic management worldwide. This review sheds light upon various biosensing technologies mainly from a material perspective by evaluating their analytical performance and suitability for point‐of‐care testing. Moreover, current challenges, opportunities, and future trends of biosensors regarding on‐site management of next pandemics are discussed.